Gender, discourse, and desire in twentieth-century Brazilian women's literature - Pinto, Cristina Ferreira, 1960- (Purdue studies in Romance literatures ;, 2004)
"This study by Cristina Ferreira-Pinto explores the poetic and narrative strategies twentieth-century Brazilian women writers use to achieve new forms of representation of the female body, sexuality, and desire. Female writers discussed include: Gilka Machado, Lygia Fagundes Telles, Marcia Denser, and Marina Colasanti. While creating new forms, these writers are also deconstructing cultural myths of femininity and female behavior. In order to understand these myths, the book also presents new readings of some male-authored canonical novels by Jose de Alencar, Machado de Assis, Manuel Autonio de Almeida, and Aluisio Azevedo."